Sliding mode control of hybrid switched systems via an event-triggered mechanism. (April 2018) - Su, Xiaojie; Liu, Xinxin; Shi, Peng; Song, Yong-Duan
Abstract: This paper is devoted to solving the problem of sliding mode control for discrete-time switched systems via an event-triggered strategy. First, a new linear switching function combined with corresponding networked sliding mode dynamics is constructed using a time-delay system design method and event-triggering scheme. Then, on the basis of the Lyapunov functional technique and the average dwell time approach, sufficient conditions for the existence of the concerned networked sliding mode control are established in terms of linear matrix inequalities. Furthermore, an event-triggered sliding mode control law is developed to drive the resultant closed-loop system trajectories into a bounded switched region and maintain them therein for subsequent periods. Finally, a verification example is given to show the effectiveness of the proposed new design techniques.